Patient safety incident analysis in healthcare: A novel curricular session for medical students - Mehta, Nishila; Sharfuddin, Nazia; Law, Marcus; Ginzburg, Amir; Chugh, Shaan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Implication StatementPatient safety incident analysis is a tool which allows for the identification of and learning from patient safety incidents, which are common in healthcare settings. The University of Toronto introduced a patient safety incident analysis session for graduating medical students in the form of a lecture and subsequent student presentations of incident analyses. Student respondents to evaluation rated the session highly and felt that feedback on their presentations was helpful to reinforce material. Medical schools can incorporate this innovative session as an interactive addition to quality improvement and patient safety curricula to provide students with hands-on experience in incident analysis.